Airborne lidar observations of Arctic polar stratospheric clouds - Poole, L. R.; Kent, G. S. (1986)
Polar stratospheric clouds (PSC's) have been detected repeatedly during Arctic and Antarctic winters since 1978/1979 by the SAM II (Stratospheric Aerosol Measurement II) instrument aboard the NIMBUS-7 satellite. PSC's are believed to form when supercooled sulfuric acid droplets freeze, and subsequently grow by deposition of ambient water vapor as the local stratospheric temperature falls below the frost point. In order to study the characteristics of PSC's at higher spatial and temporal resolution than that possible from the satellite observations, aircraft missions were conducted within the Arctic polar night vortex in Jan. 1984 and Jan. 1986 using the NASA Langley Research Center airborne dual polarization ruby lidar system. A synopsis of the 1984 and 1986 PSC observations is presented illustrating short range spatial changes in cloud structure, the variation of backscatter ratio with temperature, and the depolarization characterics of cloud layers. Implications are noted with regard to PSC particle characteristics and the physical process by which the clouds are thougth to form.